Exploring Temporal Progression of Events Using Eye Tracking. (22nd August 2015) - Welke, Tinka; Raisig, Susanne; Hagendorf, Herbert; van der Meer, Elke
Abstract: This study investigates the representation of the temporal progression of events by means of the causal change in a patient. Subjects were asked to verify the relationship between adjectives denoting a source and resulting feature of a patient. The features were presented either chronologically or inversely to a primed event context given by a verb ( to cut: long–short vs. short–long ). Effects on response time and on eye movement data show that the relationship between features presented chronologically is verified more easily than that between features presented inversely. Post hoc, however, we found that the effects of temporal order occurred only when subjects read the features more than once. Then, the relationship between the features is matched with the causal change implied by the event context (contextual strategy). When subjects read the features only once, subjects respond to the relationship between the features without taking into account the event context.